Designed Ankyrin Repeat Protein (DARPin) Neutralizers of TcdB from Clostridium difficile Ribotype 027 - Zeyu Peng; Rudo Simeon; Samuel B. Mitchell; Junjie Zhang; Hanping Feng; Zhilei Chen (mSphere, 2019)
ABSTRACT Clostridium difficile infection (CDI) is a leading cause of hospital-acquired diarrhea. In recent decades, the emergence of the “hypervirulent” BI/NAP1/027 strains of C. difficile significantly increased the morbidity and mortality of CDI. The pathogenesis of CDI is primarily mediated by the action of two toxins, TcdA and TcdB, with TcdB being the major virulent factor in humans. In this report, we describe the engineering of a panel of designed ankyrin repeat proteins (DARPins) that potently neutralize TcdB from the BI/NAP1/027 strains (e.g., TcdBUK1). The most effective DARPin, D16, inhibits TcdBUK1 with a 50% effective concentration (EC50) of 0.5 nM, which is >66-fold lower than that of the FDA-approved anti-TcdB antibody bezlotoxumab (EC50, ∼33 nM). Competitive enzyme-linked immunosorbent assays (ELISAs) showed that D16 blocks interactions between TcdB and its receptor, chondroitin sulfate proteoglycan 4 (CSPG4). The dimeric DARPin U3D16, which pairs D16 with DARPin U3, a disrupter of the interaction of TcdB with Frizzled 1/2/7 receptor, exhibits 10-fold-to-20-fold-enhanced neutralization potency against TcdB from C. difficile strains VPI 10463 (laboratory strain) and M68 (CF/NAP9/017) but identical activity against TcdBUK1 relative to D16. Subsequent ELISAs revealed that TcdBUK1 did not significantly interact with Frizzled 1/2/7. Computation modeling revealed 4 key differences at the Frizzled 1/2/7 binding interface which are likely responsible for the significantly reduced binding affinity. IMPORTANCE We report the engineering and characterization of designed ankyrin proteins as potent neutralizers of TcdB toxin secreted by a hypervirulent ribotype 027 strain of Clostridium difficile. We further show that although TcdB toxins from both ribotype 027 and VPI 10461 interact efficiently with TcdB receptors CSPG4 and Pvrl3, TcdB027 lacks significant ability to bind the only known physiologically relevant TcdB receptor, Frizzled 1/2/7.